2018
DOI: 10.3892/etm.2018.6674
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA improves diabetes mellitus via the NF‑κB‑induced AMPK signal pathway

Abstract: Diabetes mellitus (DM) is a systemic metabolic disease. Tanshinone IIA (Tan-IIA) presents potential benefits for DM. The purpose of this study was to investigate the efficacy of Tan-IIA in type 2 DM rats and explore its potential mechanism in renal cells. A type 2 DM rat model was established and administered with Tan-IIA or PBS. It was demonstrated that Tan-IIA treatment significantly reduced levels of total cholesterol, non-esterified fatty acids, total triglyceride and low-density lipoprotein cholesterol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…100 Jiang et al study revealed that the underlined compound significantly blocks the up-regulation of iNOS, matrix metalloproteinase-2 (MMP-2) as well as NF-κB/ p65 in the RNA and protein expression levels of AD rats through the NF-κB pathway to reduces AD risk. 86 In summary, the underlined data indicate a more theoretical basis for the effective treatment of tan-IIA on behalf of neurodegenerative diseases and introduce a new perspective for the AD clinical treatment.…”
Section: Anti-inflammationmentioning
confidence: 92%
See 1 more Smart Citation
“…100 Jiang et al study revealed that the underlined compound significantly blocks the up-regulation of iNOS, matrix metalloproteinase-2 (MMP-2) as well as NF-κB/ p65 in the RNA and protein expression levels of AD rats through the NF-κB pathway to reduces AD risk. 86 In summary, the underlined data indicate a more theoretical basis for the effective treatment of tan-IIA on behalf of neurodegenerative diseases and introduce a new perspective for the AD clinical treatment.…”
Section: Anti-inflammationmentioning
confidence: 92%
“…Yuan et al studies have shown that in experimental rats, the underlined compound prevents inflammatory processes and overcome symptoms of Type 2 diabetes through 5ʹ AMPK signaling cascade stimulated via NF-κB. 86 Feng et al proved that the neuropathic pain in diabetic rats' model has been lowered by tan-IIA through stimulating the Nrf2/ARE signaling cascade and attenuating the NF-kB signaling cascade. 78 Sun et al study showed that tan-IIA has remarkable cardioprotective effects given the diabetic cardiomyopathy.…”
Section: Anti-inflammationmentioning
confidence: 99%
“…e imbalance of adipose cytokines such as leptin and adiponectin secreted by adipose tissue in obese patients also aggravates the IR associated with PCOS [50]. S. miltiorrhiza Evidence-Based Complementary and Alternative Medicine extract increases the sensitivity to insulin by inducing the production and secretion of anti-inflammatory adipokines (such as APN), and it reduces inflammation and the production of proinflammatory cytokines [51,52]. Tanshinone I may also decrease fasting blood glucose concentrations by decreasing levels of interleukin-6 and tumor necrosis factoralpha and by reducing the nuclear translocation of NF-κB and the phosphorylation of Ser307 on insulin receptor substrate 1 (IRS-1) [42].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it markedly reduced the tubuloid interstitial accumulation of fibronectin and collagen I ( Jiang et al, 2016 ) and reversed the HG-induced increase in α-SMA and decrease in E-cadherin, thereby reducing renal proximal tubular fibrosis ( Cao et al, 2017 ). Tan IIA treatment increased immune cell precipitation in renal cells and improved the lipid and glucose metabolism, insulin resistance, and body weight in type 2 DM Rats ( Yuan et al, 2018 ), attenuates renal injury by reducing excessive oxidative stress and inflammation, and the mechanisms include activating Nrf2, and upregulating heme oxygenase-1 (HO-1) expression ( Liang et al, 2018 ), and enhancement of glutathione mediated detoxification pathways ( Li W. et al, 2019 ). Summarily, the affected targets by Tan IIA against urinary system diseases were shown in Figure 2 .…”
Section: Urinary Systemmentioning
confidence: 99%